2010 Fourth IEEE International Conference on Self-Adaptive and Self-Organizing Systems 2010
DOI: 10.1109/saso.2010.38
|View full text |Cite
|
Sign up to set email alerts
|

Self-Configuring Sensors for Uncharted Environments

Abstract: Sensor networks (SN) have arisen as one of the most promising monitoring technologies. The recent emergence of small and inexpensive sensors ease the development and proliferation of this kind of networks in a wide range of actualworld applications. 1 So far the majority of SN deployments have assumed that sensors can be configured prior to their deployment because the area and events to monitor are well known at design time. Nevertheless, when the purpose of an SN is to monitor the events of an environment su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Finally, Nebehay et al [2013] study the role of variation not between camera nodes, but as a characteristic of components within the object tracker in a single smart camera. Salazar et al [2010] highlight the importance of dynamic heterogeneous configurations for sensor networks deployed in uncharted environments, i.e. in scenarios about which there is a lack of a priori information.…”
Section: Heterogeneity and Variation In Self-organising Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Nebehay et al [2013] study the role of variation not between camera nodes, but as a characteristic of components within the object tracker in a single smart camera. Salazar et al [2010] highlight the importance of dynamic heterogeneous configurations for sensor networks deployed in uncharted environments, i.e. in scenarios about which there is a lack of a priori information.…”
Section: Heterogeneity and Variation In Self-organising Systemsmentioning
confidence: 99%
“…In these cases, adopting different algorithms from each other may enable them to better achieve their own local objectives. It has also been shown that such heterogeneity among nodes can lead to better achievement of system wide objectives [Campbell et al 2011;Anders et al 2012], especially when nodes can adapt independently in response to uncertainty and changes in the environment during the system's lifetime [Salazar et al 2010].…”
Section: Introductionmentioning
confidence: 99%
“…This result mirrors those from studies of heterogeneity elsewhere in multi-agent and self-organising systems, where specific benefits include adaptation to unknown situations or environments. For example, Anders et al [1] showed that heterogeneity among nodes in a network can lead to better achievement of system wide objectives, and Salazar et al [44] highlight the importance of understanding and harnessing heterogeneity when nodes can adapt independently online, in response to uncertainty and changes in the environment. In dynamic task allocation, Campbell et al [5] show that variation in agent behaviour increases the system's ability to adapt to varying stimuli.…”
Section: Heterogeneitymentioning
confidence: 99%
“…Another flavor of sensor networks works by partitioning the world according to its evolution such as the work of Salazar and colleagues [22]. In this system through a diffusion searching algorithm sensors are arranged in certain configurations.…”
Section: Sensor Networkmentioning
confidence: 99%